Penilaian terhadap kecekapan relatif industri pengagihan elektrik di Selangor menggunakan kaedah analisis penyampulan data (APD) - Ahmad, Muhammad Zaini; Ismail, Wan Rosmanira (Universiti Utara Malaysia, 2005)
This study is carried out to evaluate and identify the efficiency of the usage of resources by Tenaga National Berhad (TNB) in ten electricity distribution areas in Selangor. Based on the data of three inputs and two outputs for the year 2002,an input-oriented CCR model is used and it appears that four out of ten electricity distribution areas in Selangor are efficient. For each of the inefficient areas, this model identifies the sources and the level of inefficiency for each input and output. A set of targets for each input and output is determined for six inefficient areas. Using the average magnitude for each input, the results show that operational and maintenance expenditure is the most important input (61.86%), followed by the expenditure on main equipment (14.34%).